Crimes em assentamentos rurais : registrar ou não registrar? - Silva, Aurélio Mendanha da (2020)
This research sought to understand why residents of rural settlements in the municipality of Água Boa tend not to record criminal occurrences. Based on the theory of rational choice, we defend the hypothesis that the seated person makes a rational calculation to determine his actions of recording or not recording criminal occurrences and that variables such as, the geographical location of the settlements, the type of crime for which the individual was victim and his position in the social structure of the settlement, tend to explain why he records or does not record criminal occurrences. Regarding the methodological procedure, secondary data were used, from the collection of information in the public agencies of Incra, municipal police station of the municipality, IBGE and The Municipality of Água Boa, basically analyzing the documents and information of the systems of records of occurrences; and primary data from field research with 67 structured interviews with the settlers. The research found that the closer the settlements are to Água Boa, the more settlers tend to record occurrences. From findings such as: most criminal facts in the settlements were thefts, threats and damages and that in more structured settlements there is a greater tendency to record crime, it is possible to conclude that the determinants that motivate the individual to register or not register will depend on personal assessments, the perception of the severity of the criminal or violent fact, calculating the cost and benefit of the registration.